Discovering panic purchasing behavior during the COVID-19 pandemic from the perspective of underdeveloped countries - Muhammad Jawad; Sohail Rizwan; Saba Ahmed; Haris Bin Khalid; Munazza Naz (Cogent Business & Management, 2022)
The research seeks to uncover characteristics that affect buyers' panic purchasing behavior in COVID-19 pandemic. The data were analyzed by using the structural equation modelling of 2,697 individuals from 20 developing countries. Consumers' opinions are favourably connected with the predicted personal consequence, whereas projected community-related consequences have a negative influence on buyers' opinions. Buyers' panic purchasing intentions were found to be favourably influenced by opinion, instinctive norms, inadequacy, time restriction, and recognized competition. Furthermore, inadequacy and time restrictions were found to have a favourable effect on recognized competition but felt social detection risk had a negative effect on consumer panic purchasing intentions.
Keywords: 650; behavioural control; behavioural risk; COVID-19 pandemic; panic purchasing behavior